Determinants of rural-urban migration and its impact on migrant-sending households’ livelihood security in Gurage zone, Ethiopia - Mesfin Agza; Bamlaku Alamirew; Admasu Shibru (Cogent Social Sciences)
The study identified the variables that affect rural-urban migration and how it impacts the stability of household livelihood. Descriptive statistics, ivprobit regression, and the dose response function were all used to examine the data. Livestock holding, family size, access to information, number of cultivated fields, soil infertility, distance in kilometers to the nearest town, and distance in kilometers to the farmer training centers were the factors driving rural-urban migration. The impact of remittances on household livelihood security is positive and improved over time with relatively broad confidence ranges. It increased the livelihood security of migrant-sending households by 13.6% and the overall population by 10.99%. Higher levels of remittance had a greater impact on household livelihood security with a 40% local minimum dose. Stakeholders were given a list of policy issues and strategies for dealing with the underlying causes of rural-urban migration and maximize remittance gains.